2014
DOI: 10.2337/dc13-2480
|View full text |Cite
|
Sign up to set email alerts
|

Can a Selective PPARγ Modulator Improve Glycemic Control in Patients With Type 2 Diabetes With Fewer Side Effects Compared With Pioglitazone?

Abstract: OBJECTIVEINT131 besylate is a potent, nonthiazolidinedione, selective peroxisome proliferatoractivated receptor g (PPARg) modulator (SPPARM) designed to improve glucose metabolism while minimizing the side effects of full PPARg agonists. This placebocontrolled study compared the efficacy and side effects of INT131 besylate versus 45 mg pioglitazone HCl in subjects with type 2 diabetes (T2D). RESEARCH DESIGN AND METHODSThis was a 24-week randomized, double-blind, placebo-and active-controlled study of 0.5-3.0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 24 publications
2
57
0
Order By: Relevance
“…The diarysulfonamide non-TZD class of PPARγ partial agonists, which includes the drug INT-131, is structurally distinct from TZDs with different binding properties (Bajare et al, 2012). In mouse models, INT-131 failed to cause volume expansion and actually increased bone density, and a recent 24-week trial of 362 patients with T2DM showed equal glucose lowering efficacy to 45mg pioglitazone with evidence for less fluid retention (DePaoli et al, 2014). MBX-102 and GW1929 are two other structurally distinct non-TZD agonists with promising results in animal and cell models (Brown et al, 1999; Gregoire et al, 2009).…”
Section: More New Drug Development: Selective Partial and Dual Agonmentioning
confidence: 99%
“…The diarysulfonamide non-TZD class of PPARγ partial agonists, which includes the drug INT-131, is structurally distinct from TZDs with different binding properties (Bajare et al, 2012). In mouse models, INT-131 failed to cause volume expansion and actually increased bone density, and a recent 24-week trial of 362 patients with T2DM showed equal glucose lowering efficacy to 45mg pioglitazone with evidence for less fluid retention (DePaoli et al, 2014). MBX-102 and GW1929 are two other structurally distinct non-TZD agonists with promising results in animal and cell models (Brown et al, 1999; Gregoire et al, 2009).…”
Section: More New Drug Development: Selective Partial and Dual Agonmentioning
confidence: 99%
“…A phase IIb clinical trial has been completed for INT131, a promising non-TZD sPPARγM that improves hyperglycaemia in both animal diabetes models and T2DM patients, with effects comparable to those of TZDs but with fewer side effects than full PPARγ agonists (Motani et al, 2009; Dunn et al, 2011; Lee et al, 2012; DePaoli et al, 2014). INT131 binds to the ligand-binding pocket of PPARγ receptor, partly overlapping with the TZD binding site, but does not directly contact with Tyr 473 in helix H12, which is the binding site associated with full PPARγ agonism (Bruning et al, 2007; Einstein et al, 2008; Motani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To separate the beneficial metabolic effects from the unwanted side effects, highly potent and selective PPARa modulators (SPPARMa) and PPARc modulators (SPPARMc) are being investigated (Balint and Nagy 2006;DePaoli et al 2014;Feldman et al 2008). Dual PPAR-a/c agonists were also studied and have displayed some promising metabolic effects.…”
Section: Pparc As a Therapeutic Targetmentioning
confidence: 99%